Clinical characteristics and genotype‐phenotype correlations of 130 Chinese children in a high‐homogeneity single‐center cohort with 5α‐reductase 2 deficiency. Issue 10 (26th July 2020) - Fan, Lijun; Song, Yanning; Polak, Michel; Li, Lele; Ren, Xiaoya; Zhang, Beibei; Wu, Di; Gong, Chunxiu
Abstract: Background: Patients with steroid 5α‐reductase 2 deficiency (5α‐RD) caused by SRD5A2 (OMIM #607306) variants present variable genotypes and phenotypes. The genotype‐phenotype correlations remain unclear. Methods: We investigated genotype‐phenotype correlations of SRD5A2 variants in a large Chinese single‐center cohort. Phenotypes were categorized using the external masculinization score (EMS), urethral meatus and gonad position, and penile length‐standard deviation score. Results: Of the 130 included patients, 113 had hypospadias, and 17 had a normal urethral meatus position. Testosterone/dihydrotestosterone (T/DHT) values were not significantly associated with phenotypic severity ( p  = 0.539–0.989). Of the 31 SRD5A2 variants, including 10 novel variants, p.R227Q was the most prevalent (39.62%), followed by p.Q6* (16.92%), p.R246Q (13.46%), and p.G203S (10.38%). Compared to biallelic missense mutations, biallelic nonsense mutations were associated with a lower EMS and urethral meatus score ( p  = 0.009 and p  = 0.024, respectively). Patients homozygous for p.R227Q exhibited mild and variable phenotypes, while those homozygous for p.Q6*, p.R246Q, or p.G203S showed consistently severe phenotypes. The phenotypes were variable and milder in patients with compound heterozygosity for p.R227Q and these mutations. Conclusion: T/DHT does not predict phenotype severity. The most prevalent SRD5A2 variant in Han Chinese is p.R227Q, which is associated with milder phenotypes and greater phenotypic variability. SRD5A2 variants may significantly influence phenotypic variation. Abstract : Patients homozygous for p.R227Q exhibited mild and variable phenotypes while those with homozygous p.Q6*, p.R246Q, and p.G203S showed consistently severe phenotypes. When those mutations were compound heterozygotes for p.R227Q, the genotypes were variable and milder.